Breakthroughs in choroid plexus and CSF biology from the first European Choroid plexus Scientific Forum (ECSF) - Laura Pellegrini; Violeta Silva-Vargas; Annarita Patrizi (Fluids and Barriers of the CNS, 2024)
Abstract The European Choroid plexus Scientific Forum (ECSF), held in Heidelberg, Germany between the 7th and 9th of November 2023, involved 21 speakers from eight countries. ECSF focused on discussing cutting-edge fundamental and medical research related to the development and functions of the choroid plexus and its implications for health, aging, and disease, including choroid plexus tumors. In addition to new findings in this expanding field, innovative approaches, animal models and 3D in vitro models were showcased to encourage further investigation into choroid plexus and cerebrospinal fluid roles.